Changes in apical corneal curvature in unilateral primary Pterygium and normal adults using simulated-K and corneal irregularity measurement - Hilmi, Mohd Radzi; Musa, Nur Hidayah; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Maruziki, Nur Nabilah; Norazmar, Nur Ain; Nasir, Mardhiah Syazwani (International Islamic University Malaysia (IIUM), 2019)
Introduction: This paper aimed to describe variation in apical corneal curvature between unilateral primary pterygium and normal adults utilizing simulated-K and corneal irregularity measurement corneal indices. Methods: A total of 100 participants comprise 50 unilateral primary pterygium eyes from 50 patients and 50 normal adults were recruited in this study. Diagnosis and classification of primary pterygium were done by a consultant ophthalmologist (KMK). Standard optometric examinations were performed in all participants. Simulated-K (SimK) and corneal irregularity measurement (CIM) was objectively measured using a corneal topographer. Three measurements based on best image quality for SimK and CIM were taken by single operator in a same visit. Difference for both SimK and CIM parameters between primary pterygium and normal groups were determined via independent T-test. Results: Overall mean and standard deviation (n = 120) of SimK and CIM were found higher in primary pterygium group (9.06 ± 4.49 D and 11.48 ± 3.12) compared to normal (1.63 ± 0.67 D and 0.62 ± 0.24) respectively. Independent T-test results showed significance difference in SimK and CIM values between primary pterygium groups and normal (both P< 0.001). Conclusions: Both SimK and CIM corneal indices can be an important tool in describing and predicting changes on the corneal curvature due to pterygium progression. However, it is worth to note that the detectability of changes in anterior corneal curvature is limited to 5 mm of central corneal curvature.